1991
DOI: 10.1139/x91-142
|View full text |Cite
|
Sign up to set email alerts
|

The light interception index: a potential tool for assisting in vegetation management decisions

Abstract: Light interception by vegetation canopies surrounding white spruce (Piceaglauca (Moench) Voss) was studied for four different vegetation complexes on two sites near Prince George, British Columbia. Measurements of canopy percent cover and height, and canopy proximity to the tree, were combined to provide an index that could predict light interception by the canopy. Rates of foliage development of the different vegetation canopies studied had a significant effect on their degree of light interception over the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…Our data suggest that competitors nearest the seedlings had a disproportionate influence on growth. This follows closely with many competition-modeling approaches that use distance to modify competitive effects [1,8,23]. At both sites in this study a larger treatment area was required to maximize DBH growth compared to height growth.…”
Section: Response To Area Of Weed Controlsupporting
confidence: 58%
See 1 more Smart Citation
“…Our data suggest that competitors nearest the seedlings had a disproportionate influence on growth. This follows closely with many competition-modeling approaches that use distance to modify competitive effects [1,8,23]. At both sites in this study a larger treatment area was required to maximize DBH growth compared to height growth.…”
Section: Response To Area Of Weed Controlsupporting
confidence: 58%
“…Competition models typically use distance modifiers or a fixed-radius zone of influence to modify competitive effects [1,3,7,8,23,29,30]. Zone size varies depending on the model and species and typically ranges from 1 to 20 m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…If light had remained at the level measured in 1998 over the entire period since planting, and thus comparable among the three plantations (Table 1), the observed differences in growth could have been attributed to the species-specific competition for underground resources (DeLong 1991, Burton 1993. However, comparisons on RCI revealed no significant differences Table 1.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies on the growth of planted conifer seedlings under vegetation competition were almost exclusively concerned with plantations established after timber harvesting (e.g., DeLong 1991, Wagner and Radosevich 1991, Comeau et al 1993, Jobidon 1994, Puettmann and Reich 1995, Wang et al 2000. Although most spruce plantations on mixedwood sites have been established after timber harvesting, spruce plantations have also been established after fire disturbances in southeastern Manitoba.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover Mitchell (2003) and Newsome et al (2010) reported that diameter is an excellent response variable for competition studies because interspecific competition affects diameter growth more than it affects height growth. In many investigations (DeLong 1991;Simard et al 2001;Newsome et al 2008) it was reported that diameter responds more quickly than height to external sources whereas height responses tend not to be expressed until conifers are experiencing extreme stress and low vigour. The most appropriate functional forms between the response variables and each competition index were identified according to .…”
Section: Statistical Analysesmentioning
confidence: 99%